Are Freshwater Snails, Melanoides sp. and Invasive Tarebia granifera (Gastropoda: Thiaridae) Suitable Intermediate Hosts for Calicophoron microbothrium (Trematoda: Paramphistomoidea)? An Experimental Study - Malatji, Mokgadi P.; Myende, Nkululeko; Mukaratirwa, Samson (Frontiers in Veterinary Science, 2021)
Prosobranch snails and adult Paramphistomoidea flukes were collected from water bodies and cattle abattoir located in Mpumalanga province of South Africa, respectively. The snails were identified based on morphological characters as well as the ITS-2 and 16S markers as Melanoides sp. and Tarebia granifera, respectively, and the Paramphistomoidea flukes were identified as Calicophoron microbothrium using the ITS-1/5.8S/ITS-2 marker. After confirming identification, the snails were bred to first filial generation (F1) under laboratory conditions. Ninety snails were randomly selected from the laboratory-bred F1 snails and 25 Melanoides sp. and 20 T. granifera were exposed to C. microbothrium miracidia, and the same numbers were maintained as non-exposed controls. Results showed that C. microbothrium successfully established in Melanoides sp. and produced cercariae, and the prepatent period recorded was 21 days. Three snails shed cercariae at day 21 postexposure (PE), and rediae and free cercariae were detected in the soft tissues of one snail on dissection at day 44 PE. The same fluke did not establish in T. granifera. Melanoides sp. started producing offspring at day 7 PE, and T. granifera at day 14 PE. In conclusion, our results showed that Melanoides sp. used in this study is a suitable intermediate host for C. microbothrium under experimental conditions, and given the wide distribution of this snail species, it is important to determine its role in the natural transmission of other Calicophoron species that have been reported in South Africa.